Minsky and the narrow banking proposal: No solution for financial reform - Jan Kregel (Levy Economics Institute of Bard College, 2012)
Before the law has even been fully implemented, the inadequacies of the regulatory approach underlying the Dodd-Frank Act are becoming more and more apparent. Financial scandal by financial scandal, the realization is hardening that there is a pressing need to search for more robust regulatory alternatives. The real challenge for financial reform is to develop a vision for a financial structure that would simplify the system and the activities of financial institutions so that they can be regulated and supervised effectively. Some paths to such simplification, however, are not worth treading. Against the backdrop of renewed present-day interest in the Depression-era "Chicago Plan", featuring 100 percent reserve backing for deposits, Senior Scholar Jan Kregel turns to Hyman Minsky's consideration of a similar "narrow banking" proposal in the mid-1990s. For reasons that eventually led Minsky himself to abandon the proposal, as well as reasons developed here by Kregel that have even more pressing relevance in today's political climate, plans for a narrow banking system are found wanting.
Keywords: 330